The Role of Pharmaceutical Compounding in Promoting Medication Adherence - Maria Carvalho; Isabel F. Almeida (MDPI AG, 2022)
Pharmaceutical compounding is an important component of pharmacy practice despite its low prevalence. Several therapeutic needs can be met by a compounded medicine such as dosing adjusted for pediatric patients, special drug combinations, medicines for patients allergic to a given excipient, and medicines for orphan drugs not provided by the pharmaceutical industry. Examples of such applications are provided in this review. Adherence to medication is a critical public health issue as nonadherence to pharmacotherapy has been associated with adverse outcomes and higher costs of patient care. Adherence to therapy represents a key factor in the reduction in morbidity and mortality and optimization of the use of financial resources. The role of pharmaceutical compounding in promoting medication adherence is underexploited. The customization might represent a positive reinforcement of the initiation of the treatment, while implementation and persistence might also be favored in a pharmacy setting. However, studies addressing the influence of compounding in adherence promotion are lacking in the literature. The results of such studies could support health policies including proper regulatory framework, pharmacist training, and information to health care practitioners.